2022
DOI: 10.12688/f1000research.123468.1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of adherence to insulin and blood glucose monitoring among adolescents and young adults with type 1 diabetes in Qatar: a qualitative study

Abstract: Background: Adherence to insulin and blood glucose monitoring (BGM) is insufficient in adolescents and young adults (AYAs) with type 1 diabetes (T1D) worldwide and in Qatar. Little is known about the factors related to being aware of non-adherence and the beliefs related to non-adherence in this group. This qualitative study investigated factors related to awareness of, and beliefs about non-adherence, as well as the existence of specific action plans to combat non-adherence using the I-Change model. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 129 publications
0
5
0
Order By: Relevance
“…Parallel with this situation, our recent findings indicated that motivation and high self-efficacy among the T1DM pediatric patients mediated their ability to adjust to physical activity practices. We also discovered that a higher parental physical activity profile was associated with a higher level of physical activity among T1DM pediatric patients (Alburno et al, 2022;Michaud et al, 2017). Further, self-efficacy and participation from the patient's family members or peers were also identified as factors that drove the patient's motivation to actively engage in physical exercise practices (Wilkie et al, 2017).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Parallel with this situation, our recent findings indicated that motivation and high self-efficacy among the T1DM pediatric patients mediated their ability to adjust to physical activity practices. We also discovered that a higher parental physical activity profile was associated with a higher level of physical activity among T1DM pediatric patients (Alburno et al, 2022;Michaud et al, 2017). Further, self-efficacy and participation from the patient's family members or peers were also identified as factors that drove the patient's motivation to actively engage in physical exercise practices (Wilkie et al, 2017).…”
Section: Discussionmentioning
confidence: 74%
“…Four qualitative studies with an average number of 7, 14, and 116 T1DM participants and their parents were employed in this study (Alburno et al, 2022) (Collard et al, 2020;Fried et al, 2021;Morrow et al, 2022). We also enrolled three quantitative studies that involved 96 to 1,129 T1DM patients and their parents (Livny et al, 2020;Michaud et al, 2017;Roberts et al, 2021).…”
Section: Study Design and Participant's Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations